The Influence of the Drying Conditions on Changes in Physical and Chemical Properties of Etlingera Elatior (EE) - Habsah Alwi; N.A. Md Zaki; M.U.H. Suzihaque; S.F. Abd Karim; U.K. Ibrahim; H.Z. Abidin; M.A.A. Ramli (Archives of Metallurgy and Materials)
Etlingera elatior (EE ), commonly known as torch lily, wild ginger, and Bunga Kantan in Malaysia, is a versatile plant from the Zingiberaceae family, valued both for its ornamental blossoms and culinary uses. Infrared (IR) drying has emerged as a promising technique due to its superior drying efficiency and potential to preserve the quality of plant materials by minimizing shrinkage and maintaining material integrity. This study investigates the effects of two drying methods; IR drying and oven (OD) drying on the material characteristics of EE, specifically focusing on drying kinetics, color, shrinkage, and antioxidant capacity. EE samples were dried at temperatures ranging from 50 to 80°C until they reached a constant weight. The findings indicate that IR drying achieves a faster drying time and higher drying rate compared to OD drying. The total color change (ΔE) was lower for OD drying, with a value of 18.96, compared to 23.40 for IR drying. Regarding shrinkage, IR drying resulted in the smallest shrinkage (124.91), while OD drying showed slightly higher shrinkage (132.41). These results suggest that IR drying at 80°C is a favorable method for preserving the material characteristics of Etlingera elatior.